Jogo das artes cênicas: um jogo de tabuleiro como recurso metodológico no ensino de arte - Silva, Josenilson Cavalcanti da (2020)
The present work proposes the analysis and problem issue of the use of an authorial board game, the Game of Performing Arts, in the 8th grade class B, from the Municipal Elementary School Zumbi dos Palmares, located in the district of Mangabeira, in the municipality of João Pessoa (PB), as a methodological resource for the teaching of Performing Arts. Adding improvisation, bodily and vocal exercises, children's games, circus dynamics and performance proposals oriented by the environment of modern board games, the game offers a playful alternative for the enunciation of knowledge and artistic creations. Its conception, in the context of performance, arises from the need to find strategies that enable the development of an active, participative teaching-learning process that provides the subjects involved with the construction, individual and collective, of meaning for the educational experience-artistic. The Dutch historian Johan Huizinga and the French sociologist Roger Caillois were used as main references in the theoretical foundation, among other game theorists. This is a qualitative, ethnographic investigation, with a participatory research approach, whose main instruments of analysis will be participatory observation, note taking in a field diary, photographs, videos and reports made by students after each game match. As a result, there was a greater interest from the students in the knowledge of the curricular component Art and the analysis of the houses on the board was fruitful, with relevant notes for the future use of the game